Variação da constante de estrutura fina devido a um escalar cosmológico - Costa, Ingrid Ferreira da (2018)
In this work, we present the evolution and the consequent variation of the fine structure constant a due to a cosmological scalar, which in our case is coupled to the electromagnetic field. To do so, we use a quintessence cosmological model to demonstrate the cosmic evolution of a through a dynamical system. Then we compare its evolution with the observational limits on the variation of a. We conclude that it is useful to consider interactions between dark energy and other fields because we can use more observational data (limits on the variation of a) in order to constrain the nature of dark energy.